Untersuchung zur uterinen exfoliativen Zytologie im Frühpuerperium bei der Stute und der Kuh - Eilenberg, Ruth; Justus Liebig University Giessen (My University, 2017)
Ziel der Studie war es, die zytologische Situation in der exfoliativen Endometriumszytologie und in den Lochien während der ersten 10 Tage post partum bei Stuten und Kühen darzustellen und diese diagnostische Methode im Verlauf des Frühpuerperiums zu etablieren sowie mögliche Einflußfaktoren auf die Ergebnisse der Färbungen zu analysieren.

The objective of this study was to show the cytological situation of mares and cows in the exfoliative endometrium cytology and in the lochial during the first 10 days post partum and to establish this diagnostic method during the early puerperium. Furthermore, influencing factors on the results of the staining of slides were analyzed.
Study of the uterine exfoliative cytology during the early puerperium regarding mare and cow
Keywords: Stute; Kuh; Zytologie; Puerperium; ddc:630